Human Dignity and Judicial Interpretation of Human Rights - McCrudden, Christopher (European Journal of International Law, 2008)
The Universal Declaration on Human Rights was pivotal in popularizing the use of ‘dignity’ or ‘human dignity’ in human rights discourse. This article argues that the use of ‘dignity’, beyond a basic minimum core, does not provide a universalistic, principled basis for judicial decision-making in the human rights context, in the sense that there is little common understanding of what dignity requires substantively within or across jurisdictions. The meaning of dignity is therefore context-specific, varying significantly from jurisdiction to jurisdiction and (often) over time within particular jurisdictions. Indeed, instead of providing a basis for principled decision-making, dignity seems open to significant judicial manipulation, increasing rather than decreasing judicial discretion. That is one of its significant attractions to both judges and litigators alike. Dignity provides a convenient language for the adoption of substantive interpretations of human rights guarantees which appear to be intentionally, not just coincidentally, highly contingent on local circumstances. Despite that, however, I argue that the concept of ‘human dignity’ plays an important role in the development of human rights adjudication, not in providing an agreed content to human rights but in contributing to particular methods of human rights interpretation and adjudication.